Uptake of nitrogen, phophorus, potassium, calcium, and magnesium in carrot - Avelar, Bernardo de Carvalho; Sans, Luiz Marcelo Aguiar; Mendes, José Ferreira (Pesquisa Agropecuaria Brasileira, 2014)
Uptake of N, P, K, Ca, Mg in carrot (Daucus carota L. var. Shin Kurada) was studied for plants grown in polyethylene pots. A fertilized hydromorphic soil limed to pH 5.7 was used. Plant parts were sampled every eight days, commencing eight days after germination and continuing until the end of the production cycle. Aerial parts, edible roots, and nonedible roots were harvested separately and analyzed for N, P, K, Ca, and Mg. Macronutrient uptake by the plant was observed to be small for 32 days after germination. It then increased gradually as the plant approached maturity. Calcium was found to be concentrated in the aerial parts while magnesium was somewhat concentrated in the roots. The total amounts of phosphorus and magnesium absorbed by the plant were almost equal, increasing throughout the growing period. The concentrations of nitrogen and potassium in the aerial parts of the plant showed a marked decrease 72 days after germination.